ONE EXAMPLE OF INTERNATIONAL COOPERATION AS A CATALYST OF HIGHER EDUCATION MODERNIZATION - Tatyana O. Kochetkova; Nataliya Yu. Sirotinina (Moscow Polytechnic University, 2016)
The article describes an experience in participation of the Russian universities in the joint international project of the Tempus Programme. It is shown that international cooperation is an effective tool for the modernization of the Russian higher education system as it makes it more open and flexible.